Enhancing Mediterranean rainfed dryland productivity and resilience through legume cereal relay intercropping - Devkota Wasti, Mina Kumari (2024)
In Morocco's semi-arid rainfed regions, cereal monocropping dominates, facing threats from frequent droughts, extreme temperatures, and declining soil health. This initiative explores the integration of legumes into cereal rotations, specifically by relay-intercropping chickpeas into lentil fields. Conducted in Merchouch over three years, this innovation demonstrated improved productivity, income, and resilience. Farmers achieved dual harvests without yield losses, benefiting from drought-resistant crops and improved soil fertility. The system extended soil coverage, reduced erosion, and enhanced nitrogen fixation, promoting sustainable agriculture. Challenges include increased management complexity and the potential need for supplementary irrigation.